Application of 1-(2-Pyridylazo)-2-naphthol for Separation and Preconcentration of Trace Amounts of Cobalt(II) in Various Samples and Its Determination by Flame Atomic Absorption Spectrometry - SABER MAHANI, FATAMEH; ALI TAHER, MOHAMMAD (Asian Journal of Chemistry, 2010)
An atomic absorption spectrometric method for the determination of trace amounts of cobalt(II) after adsorption of its 1-(2-pyridylazo)-2-naphthol (PAN) complex on microcrystalline naphthalene has been developed. This complex is adsorbed on microcrystalline naphthalene in the pH range 3.0-6.0 from a large volumes of aqueous solutions of various alloys and biological samples. After filtration, the solid mass consisting of the cobalt complex and naphthalene was dissolved with 5 mL of dimethyl formamide and the metal was determined by flame atomic absorption spectrometry. Cobalt can alternatively be quantitatively adsorbed on [1-(2-pyridylazo)-2- naphthol]naphthalene adsorbent packed in a column and determined similarly. About 0.35 μg of cobalt can be concentrated in a column from 500 mL of aqueous sample, where its concentration is as low as 0.7 ng/mL. Eight replicate determinations of 1.0 μg/mL of cobalt in final DMF solution gave a mean absorbance of 0.071 with a relative standard deviation of 1.6 %. The sensitivity for 1 % absorption was 62 ng/mL in final DMF solution. The interference of a large number of anions and cations has been studied and the optimized conditions developed were utilized for the trace determination of cobalt in various alloys and biological samples.